A PRELEMINARY EVALUATION OF LIQUEFACTION POTENTIAL OF SANDY SOIL IN LEMPUING SUB-DISTRICT (A COASTAL AREA IN BENGKULU CITY) - Lindung Zalbuin Mase; Anggi Nidya Sari (Inersia: Jurnal Teknik Sipil, 2019)
In 2000 to 2009, at least two big earthquakes happened in Bengkulu. The first earthquake occurred in June 4 th, 2000 and the second one occurred in September 12, 2007. Two big earthquakes not only triggered the extensive damage of structures and infrastructures, but also triggered the attributed disaster such as liquefaction. Liquefaction occurred in Bengkulu were signed by sand boiling and lateral spreading in minimum to maximum scale in coastal area, particularly in Lempuing Sub-district. Soil condition in Lempuing Sub-District is dominated by sandy soil with shallow water table depth. Rely on the experience of earthquake and liquefaction disaster in the past, a preliminary evaluation of soil liquefaction in Lempuing Sub Districthad been conducted. The evaluation was performed to define the relationship between peak ground acceleration coefficient and relative density for variation of D of soil sample. This evaluation can be used to estimate the preliminary liquefaction potential before continue more detail analysis.